Invasive Pulmonary Aspergillosis in Hospital and Ventilator-Associated Pneumonias - Chen, Fangyue; Qasir, Danyal; Morris, Andrew Conway (Seminars in Respiratory and Critical Care Medicine, 2022)
Pneumonia is the commonest nosocomial infection complicating hospital stay, with both non-ventilated hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) occurring frequently amongst patients in intensive care. Aspergillus is an increasingly recognized pathogen amongst patients with HAP and VAP, and is associated with significantly increased mortality if left untreated.Invasive pulmonary aspergillosis (IPA) was originally identified in patients who had been profoundly immunosuppressed, however, this disease can also occur in patients with relative immunosuppression such as critically ill patients in intensive care unit (ICU). Patients in ICU commonly have several risk factors for IPA, with the inflamed pulmonary environment providing a niche for aspergillus growth.An understanding of the true prevalence of this condition amongst ICU patients, and its specific rate in patients with HAP or VAP is hampered by difficulties in diagnosis. Establishing a definitive diagnosis requires tissue biopsy, which is seldom practical in critically ill patients, so imperfect proxy measures are required. Clinical and radiological findings in ventilated patients are frequently non-specific. The best-established test is galactomannan antigen level in bronchoalveolar lavage fluid, although this must be interpreted in the clinical context as false positive results can occur. Acknowledging these limitations, the best estimates of the prevalence of IPA range from 0.3 to 5% amongst all ICU patients, 12% amongst patients with VAP and 7 to 28% amongst ventilated patients with influenza.Antifungal triazoles including voriconazole are the first-line therapy choice in most cases. Amphotericin has excellent antimold coverage, but a less advantageous side effect profile. Echinocandins are less effective against IPA, but may play a role in rescue therapy, or as an adjuvant to triazole therapy.A high index of suspicion for IPA should be maintained when investigating patients with HAP or VAP, especially when they have specific risk factors or are not responding to appropriate empiric antibacterial therapy.
Keywords: invasive pulmonary aspergillosis; ventilator-associated pneumonia; hospital-acquired pneumonia; fungal infections; critical care